2022
DOI: 10.1093/noajnl/vdac137
|View full text |Cite
|
Sign up to set email alerts
|

First multicentric real-life experience with the combination of CCNU and temozolomide in newly diagnosed MGMT promoter methylated IDH wildtype glioblastoma

Abstract: Background The randomized phase 3 CeTeG/NOA-09 trial assessed whether CCNU plus temozolomide was superior to temozolomide alone in newly diagnosed MGMT promoter methylated glioblastoma patients. Survival was significantly improved from 31.4 months (temozolomide) to 48.1 months (CCNU plus temozolomide). In view of this encouraging data, we assessed safety and efficacy of this regimen under real-life conditions. Methods We retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The study reported the safety, feasibility, and initial efficacy of this treatment protocol. A recent multi-center analysis of real-world evidence corroborated those findings, demonstrating a survival benefit for TTFields with TMZ plus CCNU [ 22 ]. These studies were the basis for expanding the CE Mark to include CCNU concomitant with TTFields and maintenance TMZ for newly diagnosed GBM patients.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…The study reported the safety, feasibility, and initial efficacy of this treatment protocol. A recent multi-center analysis of real-world evidence corroborated those findings, demonstrating a survival benefit for TTFields with TMZ plus CCNU [ 22 ]. These studies were the basis for expanding the CE Mark to include CCNU concomitant with TTFields and maintenance TMZ for newly diagnosed GBM patients.…”
Section: Introductionmentioning
confidence: 73%
“…The primary aim of this work was to study in cell cultures the effects of adding TTFields to the CeTeG regimen, a strategy with a recently identified potential clinical benefit [ 21 , 22 ]. The work described herein focused on the involvement of TTFields in DNA damage and repair as the other modalities used for treatment of GBM involve generation of DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…Median PFS of 14.4 months and median OS of 33.8 months were observed in 70 patients. 70 TTFields are a promising candidate radiosensitizer which induced an abnormal increase in mitotic catastrophe and DNA damage of cells. 32 A prospective, single-arm study that recruited 10 patients with ndGBM was conducted to assess the feasibility and safety of combined RT and TTFields therapy with maintenance TMZ and TTFields.…”
Section: New Diagnosed Glioblastomamentioning
confidence: 99%
“…A new publishment reported that the combination of TTFields and TMZ plus CCNU can provide additional survival benefits for newly diagnosed MGMT promoter methylated glioblastoma patients. Median PFS of 14.4 months and median OS of 33.8 months were observed in 70 patients 70 …”
Section: Clinical Studies Of Ttfields In Malignant Brain Tumorsmentioning
confidence: 99%
“…None of the clinical trials of these combination therapies have, so far, shown sufficient patient benefit to merit phase III trials for any tumor type or dosage regime for reasons that have yet to be established. Whether or not AGT inactivators that specifically target tumor cells [ 158 , 159 , 160 ] or other means of attenuating AGT activity, for example, tumor treating fields [ 161 ], alkylating drug combinations [ 162 ], or antisense strategies [ 163 ], will prove to be more successful remains to be seen.…”
Section: Agt In Cancer Chemotherapymentioning
confidence: 99%